Evaluation of efficacy of non-surgical periodontal treatment with usage of amoxicillin plus metronidazole for treatment of periodontitis (stage II grade B) in non-diabetic and type 2 diabetic patients - الفروي بتول; هاشم داود (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: Diabetes mellitus (DM) is one of the well-established risk factors for periodontal disease. And it has been included in the new classification scheme of periodontitis, as a grade modifier that increases the risk for future disease progression. Mechanical treatment is considered the key stone in treatment of periodontitis. Studies and researches showed best results when supporting mechanical treatment with adjunctive use of amoxicillin and metronidazole. Aim: to evaluate and compare clinical response for non-surgical treatment supported by adjunctive use of amoxicillin plus metronidazole in diabetic and non-diabetic patients with periodontitis (stage II, grade B). Materials and methods: study sample included 22 adult patients. Patients were divided into two groups. Group 1: type 2 diabetic patients, group 2: healthy patients. all patients were received non-surgical treatment, and immediately after first appointment amoxicillin (500mg) and metronidazole (500mg) were prescribed three times daily for seven days. Results: There were significant differences after treatment in both groups in terms of plaque index (PI) and bleeding on probing index (BOP) and probing depth (PD). There was improvement in clinical attachment level in non-diabetic patients only. Conclusion: mechanical non-surgical treatment supported by adjunctive use of amoxicillin plus metronidazole is effective in treatment of periodontitis (Stage II, grade B). Keywords: periodontitis, diabetes mellitus, non-surgical treatment, amoxicillin, metronidazole.